Measurement factors as determinants of purchasing decisions on fatigon hydro coco products - Andri Yulianto; Meutia Meutia; Agus David Ramdansyah; Didit Haryadi (Institute of Computer Science (IOCS), 2023)
In today's business environment, consumers find what they are looking for faster and can reach the same products. In this situation, competition is increasing in traditional areas and anywhere where communication spreads. This study aims to test and analyze the increase in purchasing decisions on Fatigon Hydro Coco isotonic drink products, by exploring conceptual models. The method used in this research is descriptive quantitative with survey. 156 respondents were taken with purposive sampling. From the results of this study, the authors concluded. The first hypothesis is that brand extension has a significant effect on brand image. The second hypothesis is that product quality has a significant effect on brand image. The third hypothesis is that brand awareness has no effect on brand image. The fourth hypothesis is that brand expansion has a significant effect on purchasing decisions. The fifth hypothesis is that product quality has a significant effect on purchasing decisions. The sixth hypothesis is that brand awareness has no effect on purchasing decisions. The seventh hypothesis is that brand image has a significant effect on purchasing decisions. This research is expected to make a theoretical contribution to the literature in this context